2013
DOI: 10.1016/j.clnu.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol epigallocatechin-3-gallate (EGCG) as adjuvant in cancer therapy

Abstract: s u m m a r yBackground & aims: Green tea catechins, especially epigallocatechin-3-gallate (EGCG), have been associated with cancer prevention and treatment. This has resulted in an increased number of studies evaluating the effects derived from the use of this compound in combination with chemo/radiotherapy. This review aims at compiling latest literature on this subject. Methods: Keywords including EGCG, cancer, chemotherapy, radiotherapy and side effects, were searched using PubMed and ScienceDirect databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
142
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(148 citation statements)
references
References 48 publications
2
142
0
4
Order By: Relevance
“…As for hormone-related cancers, such as breast and prostate cancer, EGCG interacted with the hormone receptors, delayed the development of hormone refractory tumors, and induced chemosensitization of breast and prostate cancer in vitro and in vivo (39,40). Also, EGCG could act as a protective agent against the side effects of chemotherapy, such as gastrointestinal disorders, declination of hematological parameters and immune system, development of secondary tumors, nephrotoxicity, cardiotoxicity, ototoxicity, and dysfunction of salivary glands and pulmonary fibrosis (12).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As for hormone-related cancers, such as breast and prostate cancer, EGCG interacted with the hormone receptors, delayed the development of hormone refractory tumors, and induced chemosensitization of breast and prostate cancer in vitro and in vivo (39,40). Also, EGCG could act as a protective agent against the side effects of chemotherapy, such as gastrointestinal disorders, declination of hematological parameters and immune system, development of secondary tumors, nephrotoxicity, cardiotoxicity, ototoxicity, and dysfunction of salivary glands and pulmonary fibrosis (12).…”
Section: Discussionmentioning
confidence: 97%
“…It has shown anticancer effect (including prostate, head and neck, and lung cancer) in many in vitro and in vivo studies (8)(9)(10). In addition to the antitumor activity of EGCG itself, it is reported that EGCG could enhance the efficacy of several chemotherapy drugs, as well as antagonize their toxicity (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Green tea is made from fresh tea leaves ( Camellia sinensis ). Tea is the most widely consumed beverage next to water and provides a source of the well-known polyphenols, which are associated with a reduction in cancer risk (1). After steaming or pan-frying, enzymes are inactivated to prevent the oxidation of tea polyphenols, which are also called catechins.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have shown anti-oxidative, anti-inflammatory and anticarcinogenic activities [117][118][119]. There is evidence that increased antioxidant status lowers oxidative damage to DNA, thus enhancing protection against cancer [117,120]. In addition, epidemiological data have indicated a lower incidence of cancer in subjects with higher intake of green tea [121][122][123].…”
Section: Green Tea and Coffeementioning
confidence: 99%